Colorful Online Learning Problem of Early Childhood Education During the Covid-19 Pandemic - Erni Munastiwi (State Institute of Islamic Studies Imam Bonjol Padang, 2020)
This research aims to determine the various problems of online learning at the level of early childhood education units during the COVID-19 pandemic. As for the issues among them, teachers have not all mastered IT; students tend to get bored too long studying at home. Likewise, parents are not ready to change the role of teachers at home and the policies of the central government and local governments and other issues.  This research uses a qualitative approach. Respondent consists of a teacher of 12 people and a parent of 25 people. Research location in Ponorogo Regency, East Java. The process of retrieving data using questionnaires through a google form. The results showed there were colorful problems, including 1) communication between educators, parents, and protégés, 2) the lack of costs for procurement of information technology facilities, and the price for online learning needs, 3) the right online learning method for early childhood. While the obstacles faced by parents are 1) mastery of material submitted to the child, 2) less growing the interest of the child, 3) internet network problems, 4) time accompanying the child to study online.